2001
DOI: 10.1067/mva.2001.103970
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac response and complications during endovascular repair of abdominal aortic aneurysms: A concurrent comparison with open surgery

Abstract: Hemodynamic alterations during endovascular repair were not as severe as those in patients with open surgery and indicated less myocardial stress in the former category. These findings may explain a lower incidence of myocardial ischemia that was observed during endovascular repair. A lower frequency of clinical perioperative cardiac events in patients undergoing endovascular treatment may ultimately be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 31 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…7 Although the heterogeneity associated with blood transfusion as a risk factor is large within this metaanalysis, the signal that perioperative blood transfusion is strongly associated with adverse perioperative cardiac outcomes is consistent. This is in keeping with other studies that suggest that surgery complexity 6 7 and the extent of the surgical insult 1,6,7,9,14,16,20 are strong modifiers of perioperative cardiac risk.…”
Section: Discussionsupporting
confidence: 91%
“…7 Although the heterogeneity associated with blood transfusion as a risk factor is large within this metaanalysis, the signal that perioperative blood transfusion is strongly associated with adverse perioperative cardiac outcomes is consistent. This is in keeping with other studies that suggest that surgery complexity 6 7 and the extent of the surgical insult 1,6,7,9,14,16,20 are strong modifiers of perioperative cardiac risk.…”
Section: Discussionsupporting
confidence: 91%
“…More than half of all type II endoleaks will seal spontaneously, however, and although isolated examples of aneurysm rupture on the basis of persistent type II endoleaks have been reported (1145,1146), they do not yet appear to influence the risk for rupture during 18 to 36 months of surveillance in large series of patients (1147,1148). If an intervention is necessary for the few type II endoleaks that persist or are associated with e590 by guest on May 9, 2018 http://circ.ahajournals.org/ Downloaded from ACC/AHA Practice Guidelines ACC -www.acc.org AHA -www.americanheart.org higher intraoperative cardiac index (p less than 0.01) and a lower intraoperative stroke work index (p equals 0.04) than open procedures (1162). Although the number of adverse cardiac events was comparable, postoperative electrocardiograms and transesophageal echocardiograms revealed significantly more evidence of myocardial ischemia after open operations (57% vs. 33% after endograft repair; p equals 0.01).…”
Section: Introductionmentioning
confidence: 99%
“…However, in our patient at high risk of a cardiac event, it proved extremely useful, because she had major comorbidity, which we thought precluded open repair. Cuypers et al 9 concluded that hemodynamic changes during stent-graft repair were not as severe as those that occurred during open surgery, and resulted in less myocardial stress. We also think that stent-graft repair is Wolf et al 10 and Meguid et al 11 described performing simultaneous stent-graft repair of concomitant TAA and AAA.…”
Section: Discussionmentioning
confidence: 97%